Analisa Penerapan Integral pada Fungsi Konsumsi dalam Perekonomian di Indonesia - Zahra Kamila Dinhaq Lubis; Dedek Kustiawati; Harlina Harlina; Cica Aulia Putari; Salma Renjani Ratu Utami (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In this study, the author took the title " Analysis of Integral Application of the Consumption Function in the Indonesian Economy". Economics is a science that discusses how a group of people or individuals make choices. An economic science that is often related to everyday life is consumption. One of the important components for assessing the development of the level of economic well-being of the population is the pattern of people's consumption expenditure. In Indonesia, consumption also has a very dominant role in the economy where the contribution of consumption to the Indonesian economy is very large and dominant, which is between 57.7% and 73.9% of Gross Domestic Product (GDP). Keynes' theory of consumption explains the relationship between current income (disposable income) and current consumption. This research is prepared based on the method of literature or literature study through reference books related to the preparation of the research discussed, as well as scientific articles such as journals or conference proceedings related to research problems and objectives. The consumption function in the integral is integral to its marginal consumption and conversely consumption is the first derivative of the consumption function with its integral form. In this case, the integral of the consumption function can be used as a calculation to find out the cost of consumption if there is a marginal desire as well as its income.